2010
DOI: 10.2146/ajhp080612
|View full text |Cite
|
Sign up to set email alerts
|

Unintentional i.v. injection of barium sulfate in a child

Abstract: A 17-month-old girl inadvertently received barium sulfate by i.v. injection through a CVL that was mistaken for the patient's gastrostomy tube.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…In May 2010, the accidental injection of barium sulfate through a central venous catheter in a 17-month-old was reported in the American Journal of Health Systems Pharmacists. 64 On July 15, 2010, the ISMP reported that a 19-month-old died after receiving an oral medication through a central line. 78 On a broader perspective, these are clear signals of danger for all of us who use universal connectors; on a human level, these events simply should not have happened.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In May 2010, the accidental injection of barium sulfate through a central venous catheter in a 17-month-old was reported in the American Journal of Health Systems Pharmacists. 64 On July 15, 2010, the ISMP reported that a 19-month-old died after receiving an oral medication through a central line. 78 On a broader perspective, these are clear signals of danger for all of us who use universal connectors; on a human level, these events simply should not have happened.…”
Section: Discussionmentioning
confidence: 99%
“…The nurse in the case was reported to have pending charges of manslaughter. In May 2010, the accidental injection of barium sulfate through a central venous catheter in a 17‐month‐old was reported in the American Journal of Health Systems Pharmacists 64 . On July 15, 2010, the ISMP reported that a 19‐month‐old died after receiving an oral medication through a central line 78 .…”
Section: Healthcare Industry Actionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A literature search revealed some attempts at using ZrO 2 in dental applications to better image adhesives . ZrO 2 has been shown to have better cytocompatibility than polyethylene, and has been used in orthopedic applications such as femoral head coatings in total hip replacement devices, with data showing a lower inflammatory response compared to titanium when implanted .…”
Section: Introductionmentioning
confidence: 99%
“…23,24,28 A literature search revealed some attempts at using ZrO 2 in dental applications to better image adhesives. 18,19,29 ZrO 2 has been shown to have better cytocompatibility than polyethylene, and has been used in orthopedic applications such as femoral head coatings in total hip replacement devices, with data showing a lower inflammatory response compared to titanium when implanted. [30][31][32][33] ZrO 2 -coated surfaces also possess hemocompatibility with decreased time to thrombus formation compared with uncoated surfaces or stainless steel, and could be used for a blood contacting device without inducing toxicity.…”
Section: Introductionmentioning
confidence: 99%